Research data on legislative information - Brandt, Mariana Baptista [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio (Universidade Federal de Santa Catarina (UFSC), 2020)
The data described were collected in documents of the Brazilian Chamber of Deputies in a field research and at the institution’s website. The documents analysis aimed to identify business metadata for legislative information as a step of Information Architecture methodology for business processes developed in the thesis that originated the data. The research data can be used by researchers and professionals of journalism, computer sciences, social sciences, political sciences, legistics and others, for analysis in their knowledge domain and using in another researches and applications such as information systems for legislative area.
Dados de pesquisa em informação legislativa
Keywords: Information Architecture; Legislative information; Research data